Material Extrusion Additive Manufacturing of the Composite UAV Used for Search-and-Rescue Missions - Zaharia, Sebastian-Marian; Pascariu, Ionut Stelian; Chicos, Lucia-Antoneta; Buican, George Razvan; Pop, Mihai Alin; Lancea, Camil; Stamate, Valentin Marian (MDPI AG, 2023)
The additive processes used in the manufacture of components for unmanned aerial vehicles (UAVs), from composite filaments, have an important advantage compared to classical technologies. This study focused on three-dimensional design, preliminary aerodynamic analysis, fabrication and assembly of thermoplastic extruded composite components, flight testing and search-rescue performance of an UAV. The UAV model was designed to have the highest possible structural strength (the fuselage has a structure with stiffening frames and the wing is a tri-spar), but also taking into account the limitations of the thermoplastic extrusion process. From the preliminary aerodynamic analysis of the UAV model, it was found that the maximum lift coefficient of 1.2 and the maximum drag coefficient of 0.06 were obtained at the angle of attack of 12°. After conducting flight tests, it can be stated that the UAV model, with components manufactured by the thermoplastic extrusion process, presented high stability and maneuverability, a wide range of speeds and good aerodynamic characteristics. The lack of this type of aircraft, equipped with electric motors, a traffic management system, and a thermal module designed for search-and-rescue missions, within the additive manufacturing UAV market, validates the uniqueness of the innovation of the UAV model presented in the current paper.
Keywords: UAV; additive manufacturing; composite structures; search-and-rescue missions